Penentuan Lokasi Pasang Baru Wifi.id Corner Menggunakan Metode AHP dan Algoritma Genetika (Studi Kasus : PT. Telkom Witel Kediri) - Figgy Rosaliana; Dian Eka Ratnawati; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Wifi.id corner is a location provided by Telkom Corporation to access @wifi.id network. Determining new location of wifi.id corner needs consideration and right decision. Several criterias are used to this study such as Fiber Optic network availability, level of crowdedness, location type and density level of wifi.id corner location. Analytical Hyrarchy Process (AHP) method and Genetic Algorithm are applied to solve those problems. Genetic Algorithm will optimize the weight of AHP process. This algorithm uses real code chromosome representation with length of 6 genes, each gene represent element of weighted matrix value. The Reproduction uses crossover intermediate and random mutation. In the evaluation, AHP process determine feasibility of location then will be calculated its fitness by using accuracy formula. Selection method uses elllism s election. From the result of study, optimal parameter obtained in population size of 80, number of generation 85, combination of cr 0.4 and mr 0.2 with average fitness value 0.700 or accuracy of 70%. Location feasibility will be shown to users as the final result of the system.